Prevalence and heritability of the metabolic syndrome and its individual components in a Dutch isolate: the Erasmus Rucphen Family study. Issue 9 (11th June 2008) - Henneman, P; Aulchenko, Y S; Frants, R R; van Dijk, K W; Oostra, B A; van Duijn, C M
Abstract : Background: Metabolic syndrome (MetS) is defined by a combination of abnormalities that are all individual risk factors for the development of type 2 diabetes and/or cardiovascular disease. The aetiology of MetS includes both an environmental and genetic component. We studied the prevalence and heritability of MetS and its individual components Dutch genetic isolate. Methods: The Erasmus Rucphen Family study (ERF) consists of some 3000 genealogically documented individuals from a Dutch genetic isolate. Data on waist circumference (WC), blood pressure (BP), high density lipoprotein cholesterol (HDL-C), triglycerides (TG) and fasting plasma glucose values (FPG) are available. MetS was defined according to the International Diabetes Federation (IDF) (2003) and National Cholesterol Education program Adult Panel III (NCEP ATPIII) criteria. Variance component analysis was applied to extended family data to test for evidence of heritability. Results: The prevalence of MetS in the ERF cohort ranged from 23–37% depending on MetS definition and gender considered. Low HDL-C and high WC are the main contributors to MetS. The heritability of MetS corrected for sibship effect was 10.6% (p = 0.01) according to IDF and 13.2% (p = 0.07) according to NCEP ATPIII criteria. In addition, the heritability of individual components of MetS were analysed and found to range from 21.9–42.9%. The highest heritability was found for HDL-C (42.9%, p<0.0001) and WC (37.8%, p<0.0001). In addition, WC, systolic BP, HDL-C and TG showed low to moderate genetic correlation (RhoG) between genders, whereas FPG and diastolic BP showed absolute genetic correlation between genders. Conclusion: Although the prevalence of MetS was high, the heritability of MetS in the ERF population was found to be moderate. The high heritability of the individual components of MetS indicates that the genetic dissection of MetS should be approached from its individual components.